Perfluorooctanesulfonic acid Sorption onto Polyethylene Microplastics: A Simulation-Driven Response Surface Optimization via Central Composite Design - Enyoh, Christian; Wang, Qingyue; Ovuoraye, Prosper Eguono; Lu, Senlin; Egbosiuba, Titus (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
This study demonstrates the application of response surface modeling within a Central Composite Design (CCD) to optimize the sorption processes of perfluorooctanesulfonic acid (PFOS) onto polyethylene microplastics (PE MPs), using simulation-based data from Grand Canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulations. The investigation intricately analyzes the complex interactions governing sorption phenomena (i.e. temperature and PFOS loading counts) with responses such as sorption energy, sorption density, and binding energy, employing RSM within a CCD framework. The optimization process established that the PE MPs sorption energy and sorption density were significantly dependent on PFOS loading counts in an aqueous environment. The result provides that at elevated temperature binding energy of PE MPs to Per- and polyfluoroalkyl substances was also dependent on PFOS loading counts due to associated low sensitivity temperature in the system. Optimal conditions are unveiled, enhancing sorption energy by -181.89 Kcal/mol, binding energy by -161.02 Kcal/mol, and sorption density by 1.42 g/cm³. The interaction of temperature and PFOS loading count is thoroughly examined, revealing their respective influences on sorption dynamics. These findings significantly advance our comprehension of PFOS sorption processes, fostering improved strategies for environmental remediation involving microplastic-driven sorption phenomena.